The effect of immersion silver thickness on intermetallics formed in sn-3.8ag-0.7cu leadfree solders - Saliza Azlina, Osman (2009)

(untitled)
Immersion silver is one of an alternative surface finish to printed circuit board electronic assembly in electronic packaging industry. In this study, the effect of immersion silver thickness on interfacial reactions or IMC that occur during soldering between Sn-3.8Ag-0.7Cu (SAC3807) lead-free solder on immersion silver surface finish is investigated. Solder joint reliability is also examined by performing solid state thermal aging at 150°C for up to 1000 hours. The results revealed that after reflow soldering, CusSns IMC is formed between solder and substrate while after aging treatment a new IMC was found between CufiSn5 IMC and substrate known as Cu3Sn. Aging of solder joints results in an increase of IMC's thickness and change in their morphologies to become more spherical, denser and with larger grain size. Examination of solder joints microstructures also revealed that several types and morphologies of intermetallics formed after reflow soldering and solid state ageing. However,the thickness of immersion silver surface finish metallurgy investigated was found to have n o effect on the type or morphology of intermetallic compounds formed, although with thicker silver layer the intermetallic compounds grew in thickness